Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1161/circep.114.001536
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Dermal Fibroblast Injections Slow Atrioventricular Conduction and Ventricular Rate in Atrial Fibrillation in Swine

Abstract: Background-Nonpharmacological ventricular rate control in atrial fibrillation (AF) without producing atrioventricular (AV) block remains a clinical challenge. We investigated the hypothesis that autologous dermal fibroblast (ADF) injection into the AV nodal area would reduce ventricular response during AF without causing AV block. Methods and Results-Fourteen pigs underwent electrophysiology study before, immediately, and 28 days after ≈200 million cultured ADFs (n=8) or saline (n=6)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The Askar group also showed that blunting Connexin 43 (Cx43) expression in the MF can have similar anti-arrhythmogenic effects, identifying Cx43 as a potential target for the attenuation of MF-mediated arrhythmogenesis [44]. Interestingly, the injection of autologous dermal fibroblasts into the infarct and peri-infarct areas of pigs following MI was reported to actually reduce ventricular tachycardias [45], while the group recently reported similar results in atrial fibrillation [46], disputing the theory of the "bad MF". It is suggested that the peri-infarct area is of crucial importance for the MF-mediated arrhythmogenesis.…”
Section: Myofibroblasts In Arrhythmogenesis: Bad!mentioning
confidence: 97%
“…The Askar group also showed that blunting Connexin 43 (Cx43) expression in the MF can have similar anti-arrhythmogenic effects, identifying Cx43 as a potential target for the attenuation of MF-mediated arrhythmogenesis [44]. Interestingly, the injection of autologous dermal fibroblasts into the infarct and peri-infarct areas of pigs following MI was reported to actually reduce ventricular tachycardias [45], while the group recently reported similar results in atrial fibrillation [46], disputing the theory of the "bad MF". It is suggested that the peri-infarct area is of crucial importance for the MF-mediated arrhythmogenesis.…”
Section: Myofibroblasts In Arrhythmogenesis: Bad!mentioning
confidence: 97%